The sunset years of Agnes Sharp [large type] - Swann, Leonie, 1975- (Thorndike Press large print mystery series., 2023)
"A quirky group of seniors attempts to solve one murder while covering up another--with the help of an enterprising tortoise--in this twisty, darkly funny mystery from the author of Three Bags Full. It has been an eventful morning for Agnes Sharp and the other inhabitants of Sunset Hall, a house share for the old and unruly in the sleepy English countryside. Although they have had some issues (misplaced reading glasses, conflicting culinary tastes, decreasing mobility, and gluttonous grandsons), nothing prepares them for an unexpected visit from a police officer with some shocking news. A body has been discovered next door. Everyone puts on a long face for show, but they are secretly relieved the body in question is not the one they're currently hiding in the shed (sorry, Lillith). It seems the answer to their little problem with Lillith may have fallen right into their laps. All they have to do is find out who murdered their neighbor, so they can pin Lillith's death on them, thus killing two (old) birds with one stone (cold killer). With their plan sorted, Agnes and her geriatric gang spring into action. After all, everybody likes a good mystery. Besides, the more suspicion they can cast about, surely the less will land on them. To investigate, they will step out of their comfort zone, into the not-so-idyllic village of Duck End and tangle with sinister bakers, broken stairlifts, inept criminals, the local authorities, and their own dark secrets"--